A new risk assessment approach: Safety and Critical Effect Analysis (SCEA) and its extension with Pythagorean fuzzy sets. (October 2018) - Karasan, Ali; Ilbahar, Esra; Cebi, Selcuk; Kahraman, Cengiz
Highlights: A new risk assessment method, safety and critical effect analysis, is introduced. Unlike other risk analysis techniques, both detectability and frequency are used. Pythagorean fuzzy sets are integrated to the newly proposed technique. The robustness of the proposed method is shown by comparison with other methods. An application is made to the construction sector. Abstract: In the context of occupational health and safety, risk is defined as the factor that might cause accidents in a work environment. Most techniques in the literature calculate risk magnitude based on the parameters, probability and severity . Failure Modes and Effects Analysis (FMEA) and Fine Kinney (Practical risk assessment) method incorporate the parameters, detectability and frequency to the calculation process, respectively. Although each of these four parameters has a significant role in determining the risk levels of work activities, a method considering all these parameters has not yet been developed. Therefore, in this study, a novel approach, Safety and Critical Effect Analysis (SCEA), and its extension with Pythagorean fuzzy sets are introduced to provide a more comprehensive and accurate risk assessment. In the application, the hazards in an excavation process are assessed using both SCEA and its extension with Pythagorean fuzzy sets. The obtained results are compared with FMEA and Fine Kinney methods and it is revealed that the proposed methods provide more reliable and informative outputs based on all of the essential parameters.